Beliefs About Parents' Right to Know: Domain Differences and Associations With Change in Concealment. (2nd February 2015) - Rote, Wendy M.; Smetana, Judith G.
Abstract : Parent and adolescent ( M  =   15.7 years) beliefs regarding parents' right to know (RTK) about adolescents' activities were examined in 174 middle‐class U.S. families. Mean differences and associations with latent changes in teens' concealment were assessed. RTK was greatest about risky prudential activities, least for personal activities for parents and romantic activities for teens, and higher for mothers' ratings of girls' than boys' romantic behavior. Adolescents' stronger RTK beliefs predicted lower concealment 6 months later and less increase in concealment over time, although less so for romantic issues. In contrast, mothers' stronger RTK beliefs predicted more concealment over time. For personal issues, greater teen RTK beliefs slowed increases in concealment only when parents' RTK beliefs were low.